Learner perceptions of study abroad in China: facilitators of L2 Chinese language learning and the role of individual attributes - Chen, Junming; Guo, Rongrong (Frontiers in Education, 2026)
While the number of Study Abroad (SA) students in China has increased, research on learners’ perceptions of SA experiences in China has been underexplored. Therefore, this study examines L2 Chinese learners’ perceptions of language learning facilitators during SA in China and the impacts of individual attributes (gender, proficiency, cultural background) on perceptions. A validated Likert-scale questionnaire was administered to 73 L2 Chinese learners from 22 countries, with factor analysis, nonparametric tests, and one-way ANOVAs used for data analysis. Results identified three core factors (explaining 54.937% of total variance): effective activities, supportive individuals, and key elements. Learners held more positive perceptions of the latter two more than activities. Inter-group difference analysis revealed that female learners exhibited greater recognition of most learning activities, high-level learners attached greater importance to learning opportunities and class instruction, and learners with Asian cultural backgrounds had higher recognition of language buddies. Overall, the findings demonstrate a target-oriented feature of learners’ perceptions, emphasizing in-class instruction and instructed out-of-class activities, while questioning the role of cultural events. The results call for tailored adjustments for different learners in SA programs and underscore the impact of the target language and culture on L2 learners’ perceptions. These findings provide empirical insights into the beneficial factors for language learning during SA, pointing to directions for future research.